If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = -2x + -7 Reorder the terms: 3 = -7 + -2x Solving 3 = -7 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 3 + 2x = -7 + -2x + 2x Combine like terms: -2x + 2x = 0 3 + 2x = -7 + 0 3 + 2x = -7 Add '-3' to each side of the equation. 3 + -3 + 2x = -7 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = -7 + -3 2x = -7 + -3 Combine like terms: -7 + -3 = -10 2x = -10 Divide each side by '2'. x = -5 Simplifying x = -5
| 5-3(1-x)=16 | | 0.20x+0.05(18-x)=0.10(3) | | 5k^2-6=119 | | 5(6c-5)-[3(3c-3)+3]= | | Ln(x^2)+5ln(x)-9ln(x)=-9ln | | 1+2i+3(i*i)= | | 3v^2=108 | | 24x^2+-24x+6=0 | | 0=y^2-2 | | 5log(7x-1)=25 | | 7x+7=6x+4 | | 4x-8=-36+3x | | 7z=-8 | | 60.6=x-16.8 | | 4x-5+2x+3=-38 | | 3-(1-3y)=4+7y | | 17=56-x | | kx^2-3kx+2kx=y | | -2(y+7)= | | 4(x+5)=13 | | kx^2-3kx+2kx=-1 | | (Y)-8=-5 | | kx^2-3kx+2kx=0 | | 22.7=13.3+m | | (Y)-8=5 | | logx=0.732 | | 2x^2-7=193 | | x+3=3x+91 | | 25x=25y | | X-4-2=7 | | 13x-2+13x-2=24x | | 5-3(5x+4)=38 |